ANALYSIS OF PATTERN OF ADULT PARTICIPATION IN ADULT LEARNING PROGRAMMES - Ugwu, Nneka Emilia; Orjiude, Jacinta Amazuilo (Journal of Continuing and Development Education, 2022)
The aim of this paper is to gain insight to pattern of participation in adult education programmes. Many adults lack the skill and knowledge to find their way into adult education programmes. Therefore, education policy and practice should play a role in activating and stimulating adults to learn. Adults should get equal access to learning opportunities, actually participants should be stimulated towards a satisfactory learning experience. This paper therefore, examines the concept of adult education, concept of participation, reasons for participation and non-participation in adult learning, strategies that can motivate adults to learn, recommendations on the applications of these strategies and conclusions.